2019
DOI: 10.1186/s10195-019-0537-z
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of a new-generation calcar-guided short stem in THA: clinical and radiological 5-year follow-up of 216 cases

Abstract: BackgroundIn recent years, a variety of short stems have been introduced. To date, mid- and long-term results of calcar-guided short-stem designs have been rarely available.Materials and methodsTwo hundred and sixteen calcar-guided short stems were included in combination with a cementless cup in a prospective study. Patients were allowed full weight-bearing on the first day postoperatively. Harris hip score (HHS) as well as pain and satisfaction on visual analogue scale (VAS) were assessed during a median fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 41 publications
7
22
0
1
Order By: Relevance
“…To date, to our best knowledge, no analysis of the migration pattern of a new-generation short-stem design in patients with ONFH has been published, using a validated method like EBRA-FCA. The results of the present study showed similar outcomes compared to the previously published data in patients with osteoarthritis [ 7 , 10 , 21 , 34 ]. As it was found in patients with osteoarthritis, at mid-term no stem failure and revision occurred.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…To date, to our best knowledge, no analysis of the migration pattern of a new-generation short-stem design in patients with ONFH has been published, using a validated method like EBRA-FCA. The results of the present study showed similar outcomes compared to the previously published data in patients with osteoarthritis [ 7 , 10 , 21 , 34 ]. As it was found in patients with osteoarthritis, at mid-term no stem failure and revision occurred.…”
Section: Discussionsupporting
confidence: 90%
“…But it is still unknown if this prediction can be transferred to short-stem THA as well. Previous studies have performed migration analyses in short-stem THA following the indication of primary osteoarthritis using EBRA-FCA [ 7 , 21 , 34 ]. Kutzner et al [ 34 ] investigated the optimys stem in patients with primary and secondary osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These THA related results were somewhat to be expected with regard to one of the most successful surgical procedures, if any. And our clinical results are in line with a study conducted by Kutzner et al [2].…”
Section: Discussionsupporting
confidence: 93%